How to write your undergraduate dissertation in criminology - Young, Suzanne (Routledge, 2022)
Introduction; -- What is a dissertation? -- Designing Your Criminology Dissertation -- Access and Ethical Issues in Criminology Dissertations -- Literature Reviews -- Utilising Secondary Data -- Collecting Primary Data -- Writing A Methodology Chapter -- Findings and Discussion -- Writing Up and Presenting Your Dissertation.